Recovery strategies to optimize range of motion and activities of daily living following total knee replacement in Saudi Arabia: A narrative review - Irma Liana Putri; Edy Soesanto; RNgt Amin Samiasih (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Knee osteoarthritis is highly prevalent among older adults in Saudi Arabia, with reported estimates ranging from 41% to 79%, and Total Knee Replacement (TKR) remains the definitive surgical treatment once conservative management fails. However, the long-term success of TKR depends heavily on structured post-operative rehabilitation, since surgical correction alone does not guarantee functional recovery. Purpose: This narrative review synthesizes current clinical evidence on recovery strategies following TKR, with particular emphasis on Range of Motion (ROM) progression, early mobilization, and Activities of Daily Living (ADL) recovery, while also considering the specific functional demands of the Saudi Arabian clinical context, including the high knee-flexion range required for Islamic prayer (Salah). Method: This narrative review followed the SANRA (Scale for the Assessment of Narrative Review Articles) guideline. A structured search of PubMed, MEDLINE, CINAHL, Scopus, PEDro, and Google Scholar was conducted for literature published between 2015 and 2026 using combinations of the terms